2016
DOI: 10.1080/02813432.2016.1207149
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of populations at risk of advanced melanoma in an opportunistic targeted screening project involving general practitioners

Abstract: ObjectiveThe study objective was to measure the rates of inclusion of populations at risk of advanced melanoma in a pilot targeted screening project involving general practitioners.DesignThis cross-sectional database study compared the inclusion rates of patients who signed inclusion in a targeted screening project with those of patients who did not, during a period in which both groups of patients consulted investigators.SettingData were extracted from the national healthcare insurance records in western Fran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 6 In a previous study, we demonstrated that men, older patients, patients suffering from chronic diseases, and low-income patients were less likely to benefit from screening. 35 These new study findings suggest that physicians might be more strongly involved in these populations. However, skin cancer issues would not at all be part of the reasons for medical encounters reported by these patients.…”
Section: Discussionmentioning
confidence: 84%
“… 6 In a previous study, we demonstrated that men, older patients, patients suffering from chronic diseases, and low-income patients were less likely to benefit from screening. 35 These new study findings suggest that physicians might be more strongly involved in these populations. However, skin cancer issues would not at all be part of the reasons for medical encounters reported by these patients.…”
Section: Discussionmentioning
confidence: 84%
“…A similar association was found for melanoma screening in primary practice in France, where chronic disease was associated with non-participation. 26 A Danish population-based study showed interaction between comorbidity and cancer stage with an increased mortality among patients with advanced melanoma and high comorbidity, 27 underlining the importance of a focus on comorbidity in detection and treatment of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have reported that melanoma screening is beneficial with regard to melanoma thickness, promoting screening in high-risk populations. 3–7 In addition, our team has experimented with a targeted screening programme using Self-Assessment of Melanoma Risk Score, 7 8 and the results were encouraging because many lesions were identified at an early stage. 9 10 …”
Section: Introductionmentioning
confidence: 99%